Competency-Based Islamic Education Curriculum Development Policy - Firmansyah, Fahmi; Ahmad Subagyo; Muhamad Sofian Hadi (Al-Qalam Institue, 2025)
This study aims to examine the development of a competency-based Islamic Education curriculum, with a focus on value integration strategies, the role of teachers as curriculum designers, and the challenges in assessing affective and spiritual domains. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation. Thematic analysis was applied to identify recurring patterns and themes from the data. The findings show that schools implement progressive curriculum policies, empowering teachers to contextualize religious learning and foster critical, ethical, and collaborative competencies. However, challenges persist in assessing the spiritual and affective domains due to the limited availability of assessment instruments and insufficient teacher training. This study highlights the need for authentic assessment models, emphasizes the importance of comprehensive teacher training, and provides recommendations for policymakers to address gaps in curriculum implementation and teacher development, ultimately enhancing the relevance and effectiveness of Islamic education in public schools.